(untitled) - Singh, Jagjit ([Delhi], 1966)
This book contains articless on some of the most eminent Indian scientists and their contribution to the advancement of scientific knowledge
Keywords: Scientists,Khoa học; Biography,Tiểu sử; India,Ấn Độ